2023
DOI: 10.3390/ijms24076415
|View full text |Cite
|
Sign up to set email alerts
|

Increased Biomass and Polyhydroxybutyrate Production by Synechocystis sp. PCC 6803 Overexpressing RuBisCO Genes

Abstract: The overexpression of the RuBisCO (rbc) gene has recently become an achievable strategy for increasing cyanobacterial biomass and overcoming the biocompound production restriction. We successfully constructed two rbc-overexpressing Synechocystis sp. PCC 6803 strains (OX), including a strain overexpressing a large subunit of RuBisCO (OXrbcL) and another strain overexpressing all large, chaperone, and small subunits of RuBisCO (OXrbcLXS), resulting in higher and faster growth than wild type under sodium bicarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Then, dissolved sample (0.2 mL) was mixed with 10% H 2 SO 4 (0.2 mL) and anthrone reagent (0.8 mL) before boiling for 10 min. After cooling down the samples to room temperature, the absorbance of samples was measured at 625 nm by spectrophotometer (modified from [ 4 , 7 ]). A commercial oyster glycogen was used as the standard which was prepared as similar as the sample.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, dissolved sample (0.2 mL) was mixed with 10% H 2 SO 4 (0.2 mL) and anthrone reagent (0.8 mL) before boiling for 10 min. After cooling down the samples to room temperature, the absorbance of samples was measured at 625 nm by spectrophotometer (modified from [ 4 , 7 ]). A commercial oyster glycogen was used as the standard which was prepared as similar as the sample.…”
Section: Methodsmentioning
confidence: 99%
“…There are several strategies for boosting algal biomass in order to achieve the lower carbon restriction that limits the yield of biofuel and bioproducts, including nutritional adjustment, and gene manipulation by genetic and metabolic engineering. The increased CO 2 fixation capacity, such as RuBisCO gene overexpression, and glucose utilization, has driven cyanobacteria to have better growth and photosynthesis [ 6 , 10 12 ], and be able to produce more PHB and lipids [ 4 ]. Under nitrogen or phosphorus deficiency, most cyanobacteria preferentially store carbon sources in the forms of glycogen and PHB, which are a consequence of the 2-oxoglutarate balance for carbon/nitrogen control [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that overexpressing the RubisCO-encoding genes can improve cell growth and/or the photosynthetic production of high value chemicals in S.6803 and/or S.7002 [12][13][14][15]. In this study, we attempted to improve farnesene production in S.6803 by introducing an extra copy of the RubisCO-encoding genes in the S.6803-ChrFS expressing the Picea abies α-farnesene synthase gene from a neutral site of its chromosome [9].…”
Section: The Overexpression Of the Rubisco Genes From Synechococcus P...mentioning
confidence: 99%
“…Similarly, Synechocystis sp. PCC 6803, overexpressing RuBisCO genes, produced 39% PHB when they were limited by nitrogen and phosphorus and were supplied with NaHCO 3 [77]. Oscillatoria okeni, on the other hand, is capable of producing 14% PHA with 6% PHV using only CO 2 during nitrogen limitation.…”
Section: Photoautotrophy (Sunlight)mentioning
confidence: 99%